Treatment of Venous Thromboembolism - Bates, Shannon M.; Hirsh, Jack (Thrombosis and Haemostasis, 1999)
Venous thromboembolism (VTE), which includes deep vein thrombosis (DVT) and pulmonary embolism (PE), is a common clinical problem. If untreated or inadequately treated, there is a high risk of fatal PE1 and recurrent venous thrombosis.2-4 The objectives of treatment are to prevent local extension of thrombus, embolization, and recurrent thrombosis.It is now widely accepted that VTE is a single disorder and, therefore, the treatment of venous thrombosis and PE is essentially the same. Four treatment modalities are available. Anticoagulant therapy prevents the growth of an existing thrombus or embolus, thrombolytic therapy accelerates the rate of dissolution of thrombi or emboli, caval interruption intercepts venous thrombi that break off and embolize, thereby preventing dangerous PE, and surgical therapy removes thrombi or emboli.